[Book Review] Homegoing - Louise Ling Edwards (Humaniora, 2019)
In Yaa Gyasi’s debut novel Homegoing, two sisters separated by circumstance are born in 18th-century Ghana not far from the Cape Coast Castle.  One sister, Effia, marries a white officer employed at the Castle and lives a comfortable life there with her husband and son.  The other sister, Esi, is captured during a raid on her village, marched to the Castle, and held in appalling conditions in its dungeons.  They reside in the castle together, yet without knowledge of the other’s presence or situation. The two sisters’ stories diverge when Esi is shipped to the southern plantations of the United States as part of the Trans-Atlantic Slave Trade.  The rest of the novel follows the two branches of the family through seven generations in portrait-like chapters that alternate between describing the descendants of Effia and those of Esi.  Not only does the story illustrate how the legacy of slavery impacts the two lineages generations after emancipation, but it describes an expansive scope of Black history and the relations between Africans and African-Americans through personal narrative. What is impressive about the tale is that it utilizes thorough and complex character development to move forward the histories of two nations over the span of 300 years.  The shortness of each characters’ individual story builds the intensity of each chapter packing every paragraph with emotion.  Understanding Gyasi’s deep personal connection to the story makes it clear why Gyasi was able to depict each character with such nuanced detail.  She is telling a fictionalized version of her own family history, based off of her experience straddling Ghana’s and America’s two histories.